Possibilities of multiparameter ultrasound examination in monitoring the effectiveness of radiation therapy of cervical cancer - М. A. Chekalova; V. S. Kryazheva (ABV-press, 2019)
Objective: to study the possibilities of ultrasound using modern technologies in monitoring the effectiveness of radiation therapy of cervical cancer.Materials and methods. The results of observations of 96 patients were analyzed.Results. Thirty-seven patients were diagnosed with recurrences and metastases of cervical cancer, and 59 patients were determined the criteria of full therapeutic effect.Conclusions. Multiparametric ultrasound is a highly informative method that allows diagnosing both the progression of the disease and the full therapeutic effect after radiation therapy of patients diagnosed with cervical cancer.